Stem Cells in the Oral Cavity - Luciano Silva (Studies on Stem Cells Research and Therapy - Peertechz Publications, 2015)
Stem cells have emerged in the health area as a promise for the healing of damaged tissues and replacement of organs. With their capacity of self-renewal and clonogenity, as well as their ability to  develop into many different cell types in the body, their potential seems to be unlimited, serving as a kind of cell stock for any cellular need in the human body. Nevertheless, their potential for odontology also  seems to be promising for the simple possibility of tooth reconstruction and the reestablishment of shape and function. The aim of this review is to main sites in the oral cavity where these cells can be collected.